Hypoglycaemia aggravates impaired endothelial-dependent vasodilation in diabetes by suppressing endothelial nitric oxide synthase activity and stimulating inducible nitric oxide synthase expression - He, An; Guo, Yongzheng; Xu, Zhixin; Yan, Jianghong; Xie, Lingyun; Li, Yuanjing; Lv, Dingyi; Luo, Minghao (Microvascular research, 2023)
Diabetes exacerbates vascular injury by triggering endothelial dysfunction. Endothelial nitric oxide synthase (eNOS) and inducible nitric oxide synthase (iNOS) both play major roles in endothelial dysfunction. However, effects of hypoglycaemia, the main complication of the insulin therapy to the glycemic control in diabetes, on eNOS activity and iNOS expression, and underlying mechanisms in diabetes remain unknown. Hence, we aimed to determine the effects of hypoglycaemia on eNOS activity and iNOS expression in different arterial beds of diabetic rats. Sprague-Dawley rats were subjected to Streptozotocin (STZ) combined with high fat diet (HFD) to induce diabetes and then received insulin injection to attain acute and recurrent hypoglycaemia. Immunoblotting was used to analyse the phosphorylation and O-glycosylation status of eNOS and iNOS level from thoracic aorta and mesenteric artery tissue. Indicators of oxidative stress from plasm were determined, and endothelial-dependent vasodilation was detected via wire myograph system. Hypoglycaemia was associated with a marked increase in eNOS O-GlcNAcylation and decrease in Serine (Ser)-1177 phosphorylation from thoracic aortas and mesenteric arteries. Moreover, hypoglycaemia resulted in elevated phosphorylation of eNOS at Threonine (Thr)-495 site in mesenteric arteries. Besides, changes in these post-translational modifications were associated with increased O-GlcNAc transferase (OGT), decreased phosphorylation of Akt at Ser-473, and increased protein kinase C α subunit (PKCα). iNOS expression was induced in hypoglycaemia. Furthermore, endothelial-dependent vasodilation was impaired under insulin-induced hypoglycaemia, and further in recurrent hypoglycaemia. Conclusively, these findings strongly indicate that hypoglycaemia-dependent vascular dysfunction in diabetes is mediated through altered eNOS activity and iNOS expression. Therefore, this implies that therapeutic modulation of eNOS activity and iNOS expression in diabetics under intensive glucose control may prevent and treat adverse cardiovascular events. •Our study findings demonstrate that diabetic hypoglycaemia-related endothelium dysfunction is associated with hypoglycaemia-induced increase in eNOS O-GlcNAcylation and Thr-495 phosphorylation, and decreased eNOS-Ser 1177 phosphorylation in the arteries.•Increased O-GlcNAc modification and Thr-495 phosphorylation, and decreased Ser-1177 phosphorylation of eNOS, were positively mediated by OGT and PKCα and negatively mediated by phosphorylation of Akt at Ser-473, respectively, in diabetes under hypoglycaemia.•This study is the first to report on the effect of hypoglycaemia on increased iNOS expression in normal SD rats, which may cause oxidative stress in thoracic aortas and mesenteric arteries in diabetes.